Implementation of the Surface Response to Excitation Method for Pipes - (:unkn) unknown (SPRINGER INTERNATIONAL PUBLISHING AG, 2017)
The Surface response to excitation (SuRE) method was developed to detect the defects and loading condition changes on plates without using the impedance analyzer. The SuRE method excites the surface with a piezoelectric exciter. Generally, sweep sine wave is continuously applied and surface waves are monitored with (a) piezoelectric element(s) or noncontact sensor(s). The change of the spectral characteristics is quantified by using the sum of the squares of the differences (SSD) to detect the defects. In this study, the SuRE method was implemented for detection of the defects in pipes. The surface of a pipe was excited with a continuous sweep sine wave and the dynamic response of the pipe on selected points were monitored by using a scanning laser vibrometer. The study shows that the SuRE method can be used effectively for detection of damage and estimation of its severity in pipe like structures.
Keywords: SHM; Pipe monitoring; SuRE method; Sensor networks; Guided waves; FUNDAMENTAL TORSIONAL MODE; GUIDED-WAVES; DAMAGE; REFLECTION; PROPAGATION; DEFECTS; SENSORS